Fenomenologi Proses Pembelajaran Program BTQ melalui Metode Al-Baghdadi di Madrasah Tsanawiyah Swasta Bustanul Huda Langsa - Rahmayana; Fitriani (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This research aims to find out the phenomenology of the BTQ Program Learning Process Using the Al-Baghdadi Method at the Private Madrasah Tsanawiyah Bustanul Huda Langsa. This research uses qualitative research methods with a phenomenological approach. The data sources obtained came from literature studies, events or activities, and various informants (teachers and students at MTsS Bustanul Huda Langsa). The data analysis technique used is an interactive analysis model.The results of the research concluded that, (1) There was a change in students' reading and writing of the Al-Qur'an, previously they were unable to pronounce the hijaiyah letters correctly due to the teachers' lack of desire to focus on pronouncing these letters. And now they are better able to pronounce the hijaiyah letters, especially letters that are classified as difficult, such as ط ظ ع غ ض ح ق. (2) The application of the Al-Baghdadi method in the learning process of the BTQ program has progressed to the point that students are able to understand the rules contained in the Al-Qur'an such as Makharijul Letters, Tajwid and writing rules. (3) This learning process activity is carried out by spelling each letter, this method also makes it easier for students to practice the spelling of the letters in the Al-Qur'an. The introduction of hijaiyah letters starts from alif, ba, ta and so on.